Assessment of Nurse’s Knowledge Regarding Management of Chest Tube Drainage at a Public Tertiary Care Hospital - Shakir Ullah, Najma Naz, Saeedullah, Nasir Khan, Shakir Rahman, Amir Sultan, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Chest tube insertion is a commonly performed surgical procedure in hospital practice, which is indicated in chest trauma, pneumothorax, or for use for draining of air, blood, or pus. Nurses play a role in the care of patients, like dealing with critical patients and resuscitation, so they should know about the management of chest tube drainage. Aim: To evaluate the knowledge, nursing role, and intervention of chest tube drainage. Methodology: The study design of a cross-sectional analytical study conducted in a saidu group of teaching hospitals from May 2021 to September 2021 had a sample size of 70 while using a convenient sampling technique for data collection of nurses working in the intensive care unit. Data was collected through a valid and reliable adopted questionnaire. The Chi-square test, independent sample t-test, and ANOVA were used to analyze the data. Results: Female participants (54.3%) were higher than male participants (45.7%), while the major age group was 26–30 (38.6%). The maximum nurse’s knowledge regarding chest tubes was poor (81.4%), followed by an average score (18.6%), and good was nil. In nurses' roles, the majority were poor (65.7%), while (34.3%) were average and good (nil). In nursing intervention, 68.6% were poor, the average was 31.4%, and none was good. As a result of an independent t-test, the male participants had scored higher in all three sections of the questionnaire than the female participants. Conclusion: The study concluded through ANNOVA that knowledge is highly significant (p-value 0.000) with qualification while not significant (p-value 0.225, 0.394, 0.799) with departments. Keywords: Assessment, Chest tube, Drain, Knowledge, Management, Nurses